2017
DOI: 10.3389/fevo.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Etho-Eco-Morphological Mismatches, an Overlooked Phenomenon in Ecology, Evolution and Evo-Devo That Supports ONCE (Organic Nonoptimal Constrained Evolution) and the Key Evolutionary Role of Organismal Behavior

Abstract: Since ecomorphologists have started to use explicit and taxonomically-broad frameworks in studies on the relationships between form, behavior, ecology and phylogeny they have consistently reported-often against their expectations-(1) that phylogeny is usually a better predictor of anatomy than ecology is, and (2) many cases of etho-eco-morphological mismatches. It is puzzling that such mismatches occur frequently in an evolutionary process that often leads to macroevolutionary trends and in which organisms are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…These features that mirror human malformations may have arisen over an extended period of time as chameleons began to explore locomotion away from a terrestrial environment. Alternatively, chameleons might represent “hopeful monsters”; that is, a taxon in which relatively rapid transitions leading to major morphological changes were possible and viable due to facilitated evolution/homeorhesis (reviewed in Diogo, ; Diogo, Guinard, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These features that mirror human malformations may have arisen over an extended period of time as chameleons began to explore locomotion away from a terrestrial environment. Alternatively, chameleons might represent “hopeful monsters”; that is, a taxon in which relatively rapid transitions leading to major morphological changes were possible and viable due to facilitated evolution/homeorhesis (reviewed in Diogo, ; Diogo, Guinard, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the above mentioned studies revealed that species that inhabit the same ecological niche converge in shape [ 9 , 13 15 , 17 , 18 ]. This seems to be a common pattern also among terrestrial vertebrates [ 23 26 ], although mismatches of form and function triggered by behavioural plasticity and diverse constraints exist as well [ 27 ]. In terrestrial vertebrates the impact of phylogenetic dependence on shape similarity among closely related taxa has been tested explicitly [ 26 , 28 , 29 ] and several studies have examined these in teleost fishes, as well, using individual adaptive traits for ecological niches [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, evolutionary ancestry appears to explain a significant portion of orofacial cleft diversity in Vespertilionidae, as evidenced by strong phylogenetic signal in 3D landmark data. This indicates that cleft evolution may be, at least partially, constrained by intrinsic factors linked to common ancestry and without a clear adaptive value within the context of feeding function in vesper bats (Alberch, 1989;Diogo, 2017;Galis, 1999). After taking phylogenetic autocorrelation into account, we found that the shape of clefts did not vary with 3D skull shape, but cleft mediolateral width and anteroposterior length were correlated with skull shape in vespertilionid bats.…”
Section: Discussionmentioning
confidence: 76%
“…Reduction of the premaxillary bone is a synapomorphy of Chiroptera (Giannini and Simmons, 2007;Hutcheon and Kirsch, 2006;Orr et al, 2016;Simmons and Geisler, 1998). Therefore, the morphospace within which the bat rostrum can evolve may be biased by conserved genetic and developmental factors, resulting in the repeated evolution of orofacial clefts as one of a limited set of possible morphologies (Alberch, 1989;Diogo, 2017;Felice et al, 2018;Galis, 1999). Additionally, the prevalence and repeated evolution of naturally occurring orofacial clefts in bats may indicate that this trait is adaptive for a function other than biting, or that their evolution is the consequence of a trade-off with another function that increases overall fitness.…”
Section: Discussionmentioning
confidence: 99%